CONCEPTUAL METONYMY WHOLE FOR PART AND PART FOR WHOLE IN THE KOREAN DRAMA “THE GLORY”: A COGNITIVE SEMANTIC STUDY: METONIMI KONSEPTUAL WHOLE FOR PART DAN PART FOR WHOLE DALAM DRAMA KOREA “THE GLORY”: KAJIAN SEMANTIK KOGNITIF - Ni Gusti Ayu Dhyani Widyadari; Elvi Citraresmana; Cece Sobarna (Jurnal Kata, 2023)
The lack of research on metonymy and the number of Korean dramas raise issues that occur in South Korea make researchers want to study more deeply about how the conceptualization of metonymy is shown in an issue in Korea through drama. This study aims to identify and describe what conceptual metonymy is used and how to map the conceptual metonymy shown in the drama “The Glory” using cognitive semantic studies. This study used a descriptive qualitative approach with a data collection method of listening and note taking techniques as well as MIPVU (Metaphor Identification Procedure Vrije Universiteit) procedures developed for metonymy by Berri and Bregant (2015) as a data analysis method. The simak catat technique is used to see and record the use of conceptual metonymy contained in the drama “The Glory”. The method of presenting the data used is formal and informal methods because the data contained in this study is presented in the form of tables and descriptive analyses regarding conceptual metonymy. The findings obtained in this study were in the form of 23 data of conceptual metonymy found which included 12 data of WHOLE FOR PART metonymy and 11 data of PART FOR WHOLE metonymy. In the drama “The Glory” conceptual metonymy is used to name events that occur, mention the use of terms, mention the characteristics and circumstances of a person, and substitute the mention of objects or place.